2015
DOI: 10.1016/j.bbr.2015.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Role of whiskers in sensorimotor development of C57BL/6 mice

Abstract: The mystacial vibrissae (whiskers) of nocturnal rodents play a major role in their sensorimotor behaviors. Relatively little information exists on the role of whiskers during early development. We characterized the contribution of whiskers to sensorimotor development in postnatal C57BL/6 mice. A comparison between intact and whisker-clipped mice in a battery of behavioral tests from postnatal day (P) 4 to 17 revealed that both male and female pups develop reflexive motor behavior even when the whiskers are cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 62 publications
4
52
0
Order By: Relevance
“…The AIS scaffolding protein βIV-spectrin, a wellestablished target for morphometrical analysis of the AIS (Gutzmann et al, 2014;Kim et al, 2019;Schlüter et al, 2017) was utilized, while immunoblot analysis was directed against the known isoforms of ankG, the main regulator of AIS assembly and maintenance (Jenkins et al, 2015b;Rasband, 2011). In line with previous reports (Galiano et al, 2012;Gutzmann et al, 2014), we found that the AIS elongated during the early postnatal period until the end of the second postnatal week, a time at which mice begin active whisking to explore their environment (Arakawa and Erzurumlu, 2015), indicated by grey boxes in Fig.1B). With the onset of active whisking behavior, however, a significant shortening of AIS length was observed both in pyramidal neurons of layers II/III and V ( Fig 1B).…”
Section: The Ais Undergoes Periods Of Structural Plasticity During Desupporting
confidence: 82%
See 1 more Smart Citation
“…The AIS scaffolding protein βIV-spectrin, a wellestablished target for morphometrical analysis of the AIS (Gutzmann et al, 2014;Kim et al, 2019;Schlüter et al, 2017) was utilized, while immunoblot analysis was directed against the known isoforms of ankG, the main regulator of AIS assembly and maintenance (Jenkins et al, 2015b;Rasband, 2011). In line with previous reports (Galiano et al, 2012;Gutzmann et al, 2014), we found that the AIS elongated during the early postnatal period until the end of the second postnatal week, a time at which mice begin active whisking to explore their environment (Arakawa and Erzurumlu, 2015), indicated by grey boxes in Fig.1B). With the onset of active whisking behavior, however, a significant shortening of AIS length was observed both in pyramidal neurons of layers II/III and V ( Fig 1B).…”
Section: The Ais Undergoes Periods Of Structural Plasticity During Desupporting
confidence: 82%
“…The significant reduction in AIS length seen from P15 (in layer II/III) and P10 (in layer V) onwards coincides with the onset of explorative, active whisking behavior in mice (Arakawa and Erzurumlu, 2015). A similar AIS maturation pattern (early postnatal elongation, followed by length reduction and subsequent stable adult length) was previously described for the primary visual cortex and shown to be regulated by the onset of vision at P13-14 (Gutzmann et al, 2014).…”
Section: Ais Elongation Is Triggered By Long-term Sensory Deprivationsupporting
confidence: 71%
“…While TH after HI preserved sensorimotor processing in female mice, TH preserved motor balance and coordination in male mice. Since intact sensorimotor processing is necessary for development of exploratory behaviors, including food seeking [76], we hypothesize that these very refined differences in protection of various motor domains with TH may account for sexual dimorphism in growth seen in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, active whisking fully matures during the first three postnatal weeks. Vibrissae movements transition from spontaneous unilateral muscle twitches of the whisker pad in the first week after birth to regular bilateral rhythmic sweeps at the end of the third postnatal week (Arakawa & Erzurumlu, 2015;Grant, Mitchinson, & Prescott, 2012;Tiriac, Uitermarkt, Fanning, Sokoloff, & Blumberg, 2012). During the same period, cortical connectivity undergoes major reorganization, including the maturation of connectivity between layer (L) 4 and L2/3 (Feldmeyer, Lübke, Silver, & Sakmann, 2002;Stern, Maravall, & Svoboda, 2001) and strengthening of local connectivity within L2/3 (Clem & Barth, 2006;Clem, Celikel, & Barth, 2008;Feldmeyer, Lübke, & Sakmann, 2006;Itami & Kimura, 2012;Wen & Barth, 2011).…”
Section: Introductionmentioning
confidence: 99%